2021
DOI: 10.1177/03913988211006715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender in patients with continuous-flow left ventricular assist device therapy in end-stage heart failure

Abstract: Background: There is an ongoing debate about the influence of the female gender on postoperative outcomes after durable left ventricular assist device (LVAD) implantation. Despite the differences in pathophysiology of heart failure in females, therapy concepts are the same as in the male population. The aim of this study was to investigate the role of the female gender in surgical heart failure therapy. Materials and methods: Between August 2010 and January 2020, 207 patients were treated with durable LVAD at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Sadly, recent reports examining sex-related differences following LVAD implantation suggest a disparity in outcomes continues to exist. Zubarevich et al reported on a 2:1 propensity matched study of 111 patients (74 male, 37 female) who had undergone durable LVAD implant between 2010 and 2020 [16 ▪ ]. While there were no differences in survival found, females had a greater incidence of LVAD thrombosis (13.5 vs. 0%, P = 0.001) and prolonged need of renal replacement therapy >90 days (56.8 vs. 33.8%, P = 0.021) compared to males in the follow-up period.…”
Section: Relationship Of Sex On Outcomes Of Durable Left Ventricular ...mentioning
confidence: 99%
“…Sadly, recent reports examining sex-related differences following LVAD implantation suggest a disparity in outcomes continues to exist. Zubarevich et al reported on a 2:1 propensity matched study of 111 patients (74 male, 37 female) who had undergone durable LVAD implant between 2010 and 2020 [16 ▪ ]. While there were no differences in survival found, females had a greater incidence of LVAD thrombosis (13.5 vs. 0%, P = 0.001) and prolonged need of renal replacement therapy >90 days (56.8 vs. 33.8%, P = 0.021) compared to males in the follow-up period.…”
Section: Relationship Of Sex On Outcomes Of Durable Left Ventricular ...mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Due to the contact formed between blood and the artificial surfaces, patients need lifelong anticoagulation treatment. [27][28][29] Most importantly, with an incidence of up to 20% of patients, [30,31] the risk of thrombosis (Figure 1a) eventually resulting in a stroke remains a serious complication for VAD recipients. Moreover, due to the still necessary external power supply, patients may suffer further complications such as driveline infections.…”
Section: Introductionmentioning
confidence: 99%